Exact and exclusive electron localization indices within QTAIM atomic basins. Issue 20 (10th April 2018) - de Lange, Jurgens H.; Cukrowski, Ignacy
Abstract : Novel measures of electron (de)localization within the Quantum Theory of Atoms in Molecules (QTAIM) atomic basins are presented which, unlike orthodox localization indices (LIs), are fully exclusive and can be easily visualized. This work shows that QTAIM‐defined LIs describe a portion of interatomic delocalized electrons; hence, the chemical/physical interpretation of orthodox LIs is misleading. Using the recently introduced Fragment, Atomic, Localized, Delocalized, and Interatomic (FALDI) density decomposition technique we derive two novel sets of LIs and delocalization indices (DIs), by accounting for the overlap between localized and delocalized density functions. The FALDI‐based LIs and DIs perfectly recover chemically expected core and bonded electron count. Usefulness of new (de)localization indices and their 3D representations were demonstrated on a number of examples, including formamide and benzene. We therefore expect that the scheme reported in this work will provide a valuable stepping stone between classical conceptual chemistry and quantum chemical topology. © 2018 Wiley Periodicals, Inc. Abstract : A new method for calculating and visualizing electron (de)localization for atoms is presented. The resulting indices present exclusively (de)localized electrons that correspond to classically expected values for atoms involved with typical chemical bonds. The authors explain that traditional QTAIM‐based (de)localization indices are non‐exclusive and ambiguous in their physical meaning.